2008
DOI: 10.1038/nature06531
|View full text |Cite
|
Sign up to set email alerts
|

Structure and mechanism of the M2 proton channel of influenza A virus

Abstract: The integral membrane protein M2 of influenza virus forms pH-gated proton channels in the viral lipid envelope. The low pH of an endosome activates the M2 channel before haemagglutinin-mediated fusion. Conductance of protons acidifies the viral interior and thereby facilitates dissociation of the matrix protein from the viral nucleoproteins--a required process for unpacking of the viral genome. In addition to its role in release of viral nucleoproteins, M2 in the trans-Golgi network (TGN) membrane prevents pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

58
1,244
7
8

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 941 publications
(1,327 citation statements)
references
References 38 publications
58
1,244
7
8
Order By: Relevance
“…30,31 The X-ray structures confirm the most important features observed in our MD simulations (Supporting Information Figure S6). In particular, the channel pore "is most constricted near Val27", providing direct support of our proposal for a secondary gate.…”
supporting
confidence: 77%
“…30,31 The X-ray structures confirm the most important features observed in our MD simulations (Supporting Information Figure S6). In particular, the channel pore "is most constricted near Val27", providing direct support of our proposal for a secondary gate.…”
supporting
confidence: 77%
“…An AM2 construct including residues 18 to 60, AM2(18-60), in dihexanoylphosphocholine (DHPC) detergent micelles met these requirements. This construct, which includes the TM domain as well as 15 residues of the C-terminal extension forms a very stable tetramer and yields high-quality NMR spectra (Schnell and Chou, 2008). It has also been confirmed that when reconstituted into liposomes, AM2(18-60) exhibits specific proton conductance that can be inhibited by as low as 10 μM of rimantadine .…”
Section: Structures Of the Am2 Channel Of Influenza Amentioning
confidence: 82%
“…In 2008, using solution NMR spectroscopy, Schnell and Chou determined the first atomic resolution structure of the closed AM2 channel in the presence of the anti-influenza drug rimantadine (Schnell and Chou, 2008). One of the main challenges of solution NMR study of membrane proteins is finding a combination of protein construct and detergent system that both supports the native function of the protein and results in high quality NMR spectra.…”
Section: Structures Of the Am2 Channel Of Influenza Amentioning
confidence: 99%
See 2 more Smart Citations